A case report of juvenile hyaline fibromatosis - Mohammed H. Abduljabbar (Wolters Kluwer Medknow Publications, 2014)
Juvenile hyaline fibromatosis (JHF) is a rare, autosomal recessive disease characterized by early onset papulonodular skin lesions, soft tissue masses, joint contractures, gingival hypertrophy, stunted growth and osteolytic bone lesions. Histopathological examination of the cutaneous lesions is unique and characterized by an accumulation of an amorphous, hyaline material in the dermis with increased number of fibroblasts. Herein, we report an 11 year-old girl who presented with papulonodular lesions on the scalp, chin, ears, elbows, knees, back and perianal skin. She had gingival hypertrophy and contractures of the elbows, hips, knees and ankles.